Antibodies to choroid plexus in senile dementia of Alzheimer's type. Issue 9 (September 1992) - Serot, J M; Béné, M C; Gobert, B; Christmann, D; Leheup, B; Faure, G C
Abstract : AIMS: To investigate whether autoantibodies to choroid plexus are present in human senile dementia. METHODS: Serum samples from 40 elderly people presenting with characteristic, diagnostic criteria of senile dementia of Alzheimer's type and 20 age matched healthy controls were tested by indirect immunofluorescence for the presence of autoantibodies to choroid plexuses, using frozen sections of rat or human fetal brain tissue. RESULTS: Significant labelling of choroid plexus basement membrane was observed in 17 of the 40 samples from patients with senile dementia; in the control series one sample of rat but not human plexus labelled positively (p < 0.01). CONCLUSIONS: The antibodies identified in this series of patients with Alzheimer's disease suggest that autoimmune mechanisms might be responsible for some of the changes in cerebrospinal fluid production described in this disorder.